Atherothrombotic Risk Stratification and the Efficacy and Safety of Vorapaxar in Patients With Stable Ischemic Heart Disease and Previous Myocardial Infarction. Issue 4 (26th July 2016) - Bohula, Erin A.; Bonaca, Marc P.; Braunwald, Eugene; Aylward, Philip E.; Corbalan, Ramon; De Ferrari, Gaetano M.; He, Ping; Lewis, Basil S.; Merlini, Piera A.; Murphy, Sabina A.; Sabatine, Marc S.; Scirica, Benjamin M.; et al.
Abstract : Background: Patients with stable ischemic heart disease and previous myocardial infarction (MI) vary in their risk for recurrent cardiovascular events. Atherothrombotic risk assessment may be useful to identify high-risk patients who have the greatest potential to benefit from more intensive secondary preventive therapy such as treatment with vorapaxar. Methods: We identified independent clinical indicators of atherothrombotic risk among 8598 stable, placebo-treated patients with a previous MI followed up for 2.5 years (median) in TRA 2°P-TIMI 50 [Thrombin Receptor Antagonist in Secondary Prevention of Atherothrombotic Ischemic Events–TIMI 50]. The efficacy and safety of vorapaxar (SCH 530348; MK-5348) were assessed by baseline risk among patients with previous MI without prior stroke or transient ischemic attack for whom there is a clinical indication for vorapaxar. End points were cardiovascular death, MI, or ischemic stroke and GUSTO (Global Use of Strategies to Open Occluded Coronary Arteries) severe bleeding. Results: The 9 independent risk predictors were age, diabetes mellitus, hypertension, smoking, peripheral arterial disease, previous stroke, previous coronary bypass grafting, heart failure, and renal dysfunction. A simple integer-based scheme using these predictors showed a strong graded relationship with the rate of cardiovascular death/MI/ischemic stroke and the individual components ( P for trend <0.001 for all). High-risk patients (≥3 risk indicators; 20% of population) had a 3.2% absolute risk reduction in cardiovascular disease/MI/ischemic stroke with vorapaxar, and intermediate-risk patients (1–2 risk indicators; 61%) had a 2.1% absolute risk reduction ( P <0.001 each), translating to a number needed to treat of 31 and 48. Bleeding increased across risk groups ( P for trend<0.01); however, net clinical outcome was increasingly favorable with vorapaxar across risk groups. Fatal bleeding or intracranial hemorrhage was 0.9% with both treatments in high-risk patients. Conclusions: Stratification of baseline atherothrombotic risk can assist with therapeutic decision making for vorapaxar use for secondary prevention after MI. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00526474. Abstract : Supplemental Digital Content is available in the text.